الأسلوب المعرفي (الاندفاع-التروي) لدى طلاب المدارس الثانوية للمتميزين (Journal Of Educational and Psychological Researches, 2016)
What we observe from the weakness of the students in some of different subjects may be due to that students are learning these traditional methods and competing to acquire the mark, and attain their teachers' interest ,then their only aim becomes the academicsuccess, and this is whatcontradicts the modern educational philosophy.          Education needs to be providing it with new ideas and methodologies toprepare an emerging demonstrated scientific reason to distance them from the tradition and indoctrination that do not create generations able to address theexpected problems.The cognitive behavior of reflectiveincludes planning skills, and self-regulation, monitoring,evaluation and the sense of using and choosing cognitivestrategies ,and they aremetacognitive skills,and this, on the contrary, behavior ofimpulsive who lack such skills (Al-nassaj,3:2002).          The current research has focused  on secondary school students and junior high specially the distinct students.           The importance of the current search raises through the variable that researchers are trying to study a cognitive style (impulsivity-reflection)which is one of these styles reliable basis for discrimination between individuals in their responses to different life situations and the extent of their competence and their accuracy.Scale of cognitive style (impulsivity-reflection )has been built to achieve the objectives of the current search at high school students of the distinct . researcher has read out the psychometric properties of the same scale .The current research has reached the following results:4% impulsive ,and 15% reflective ,and 70%betwixt and between.There is no statistically significant difference between males and females in cognitive style (impulsivity-reflection).The researchers found a number of recommendations and proposals.